PROYEKSI KEBUTUHAN AIR BERSIH DI WILAYAH KECAMATAN DENPASAR SELATAN KOTA DENPASAR DALAM 10 TAHUN MENDATANG - Frederikus Marung; Ida Bagus Suryatmaja; Krisna Kurniari (Fakultas Teknik Universitas Mahasaraswati Denpasar, 2021)
Along with the grave of the population of Denpasar City more especially the South Denpasar sub-district from year to year resulted in an increase in the amount of clean water needs. The increase in clean water needs is certainly necessarily anticipated early to avoid the potential lack of clean water in the future. For this reason, a study is needed to find out how the estimated clean water needs in the next future 10 years. Before calculating, first is to know the estimated population in the next 10 years or 2030. To calculate data on the number of population in the last five years to find the average population growth. Using the geometry method, then calculated the estimated population in 2030. The result is, the population in 2030 was 408499 people. Meanwhile, data is also needed related to the current average of clean water. The data was obtained through a survey using the questionnaire method. The sample in this survey was determined using the Slovin formula, where the number of PDAM water customers in 2020 was 19788 home connections and by using a tolerance limit of 10%, then the number of respondents was 100 home connections. Of the 100 respondents, the result is the average use of clean water of 120 liters/person/day. With this data, the need for clean water needs in the next 10 years with service coverage is 80% of the total population. The result is, the total clean water requirement in 2030 was 668.7756 liters/second. With this enormous need, water sources are needed with high production capacity to meet the needs of 2030.